Contract Law in an Era of Technology: Examining Liability in Smart Contract Transactions - Edema, Tega (ABUAD Law Journal, 2023)
The growing use of smart contracts in a wide range of transactions has raised a deluge of legal issues, including allocation of liability in such transactions. In many circumstances, using smart contracts involves a range of legal risks that might be distributed beyond the contractual parties to other parties, such as the developers of the smart contract code. While smart contracts have the potential to disrupt the current legal and transactional status quo, notorious occurrences such as attacks on Ethereum or Bitcoin platforms highlight the need to properly dissect the issue of liability and rightly apportion liability where it falls. This also includes working on any lapses in the existing legal and transactional framework to cater for these issues. This article sets out to examine the validity of smart contracts in the light of existing contract law principles. It examined the legal regime and development of smart contracts in Nigeria. It further discussed the problem of allocation of liability associated with smart contracts. It made certain propositions on how these issues could be tackled including the amendment of existing legal framework to aptly provide for and regulate the smart contracts era particularly in Nigeria. The doctrinal method of research was employed to dissect the issues raised and discussed in the article. Relevant texts were scrutinized and analyzed to arrive at the findings and recommendations contained in the article.